Penerapan Siklus Belajar 5E Dengan Media PowerPoint Untuk Meningkatkan Aktivitas Belajar dan Hasil Belajar Siswa - Kaesta Uri Winggi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The purpose of this research is increase students' activities and the result of learning using Learning Cycle 5E with PowerPoint and use WhatsApp Group for discussion and Google Classroom for assignments. This research is an Action Research using a mixed methods approach with quantitative and qualitative analysis. Use the model by Kemmis and Mc. Taggart, has 4 activities in each cycle, are planning, action, observation, and reflection. This research was conducted at SMK Negeri 1 Nganjuk. The research subjects were 36 students of class X-TKJ-2. The object of research is student activities and the result of learning. The data collection techniques were carried out by using test and non-test. The test is done by giving assignments at the end of the cycle. While non-test is observations by students when learning to dare. Data analysis is presented in the form of tables and graphs, with qualitative data analysis in the form of words or symbols and quantitative data analysis in numbers.The results of student activities in the pre-cycle is 33%, the first cycle increased by 10%, the score was 43%, in Cycle II is increased by 37%, the score was 80%, beyond 75%, and has high criteria. For the result of learning in the pre-cycle the percentage of student learning is 28%, in Cycle I it is 36%, Cycle II increases to 83% of students who have scores above the KKM. The conclusion is that PowerPoint with Learning Cycle 5E can improve student learning activities and the result of learning.